The Influence of Sense of Place on Elementary School Students’ Creativity During the COVID-19 Pandemic: The Mediating and Buffering Effects of Psychological Resilience - Xu, Yanhua; Wang, Qiaoling; Zhang, Dongmei; Lin, Peiying (Frontiers in Psychology, 2022)
Purpose To understand the relationship between sense of place and creativity and the mechanisms that affect this relationship, the researchers constructed a mediation model to examine the effect of sense of place on creativity and the mediating role of psychological resilience in elementary school students during the COVID-19 pandemic. Methods A total of 1,711 students in an elementary school in Beijing, China, were surveyed using Chinese-language versions of the Sense of Place Scale, the Psychological Resilience Scale-Short Version, and the Innovative Behavior Inventory. SPSS (version 23) and PROCESS plug-in (version 3.3) were used for correlation and mediation analyses. Results (1) Correlation analysis revealed that sense of place was positively related to psychological resilience (r = 0.445, p < 0.01) and creativity (r = 0.590, p < 0.01). (2) Psychological resilience was also positively correlated with creativity (r = 0.625, p < 0.01). (3) Further, after controlling for gender and grade level, it was found that sense of place directly predicted creativity and that sense of place also indirectly predicted creativity through psychological resilience. The direct effect (0.45) and the mediating effect (0.23) accounted for 65.95 and 34.05% of the total effect, respectively. Conclusion The results demonstrate that sense of place is a positive predictor of creativity and can play a facilitating role to some extent. Moreover, psychological resilience is a mediating factor, acting as a buffer between sense of place and creativity. These results contribute to a more comprehensive understanding of the mechanisms influencing creativity.